Löfgren Syndrome with Hypercalcemia and Neuroendocrinological Involvement: A Case Report - Almaguer-Morales, Daniel; Hinojosa-González, David E.; Garza-Alpirez, Alejandro (Current Rheumatology Reviews, 2020)
Background: Sarcoidosis is a systemic inflammatory disease of unknown etiology that can affect virtually any organ. Löfgren syndrome, characterized by erythema nodosum, hilar lymphadenopathy, fever and polyarthritis, represents only 20-30% of the cases of sarcoidosis. Only 2- 10% of the cases feature hypercalcemia. Case: The case of a 42-year-old Hispanic woman with a history of erythema nodosum and three weeks of nausea, emesis, constipation, asthenia, adynamia, polydipsia, and somnolence, concomitant with hypercalcemia, but normal parathyroid hormone (PTH) and 25-hydroxyvitamin D has been presented. The initial diagnostic approach was based upon the suspicion of multiple myeloma or bone metastases; however, further findings of bilateral hilar lymphadenopathy, elevated serum angiotensin-converting enzyme (ACE) and a right inguinal lymphadenomegaly suggested an alternate diagnosis. Biopsy of the latter supported sarcoidosis as the diagnosis. She was successfully treated in the hospital with zoledronic acid and as an outpatient with immunosuppressive therapy. Persistence of a previously undisclosed symptom of oligomenorrhea led to the detection of hyperprolactinemia secondary to hypophyseal infiltration, refractory to immunosuppressive therapy but with an adequate response to cabergoline. Conclusion: This case strays from Löfgren Syndrome’s expected behavior, presenting a more progressive, multisystemic disease. This case report was written in adherence to the CARE guidelines of 2013 to include information in it.
Keywords: cabergoline